Pemantauan Iklim Mikro di Perpustakaan Universitas Indonesia - Syam'aeni, Muhammad Asyep; Adriani Salim, Tamara (Perpustakaan Universitas Gadjah Mada, 2025)
The preservation of library collections, especially those made from organic materials such as paper and leather, is an important challenge in information management. Environmental factors such as uncontrolled temperature and relative humidity can accelerate the degradation of collections. This study aims to analyze the microclimate conditions in the manuscript collection room of the Universitas Indonesia (UI) Library to evaluate the risks to collection preservation. Temperature and relative humidity monitoring was carried out continuously for one month using data loggers in the UI Library's manuscript collection room. The data obtained were analyzed to calculate the Equivalent Lifetime Multiplier (eLM) value, an index that measures the impact of temperature on the lifespan of collections. The results showed that the average temperature in the collection room was 28.1°C, with an average relative humidity of 70.2%. The eLM value obtained was 0.209, indicating that the collection is at high risk of degradation with an effective lifespan of only 20.9% of its ideal lifespan. Significant temperature and humidity fluctuations were also observed during the monitoring period, especially when the HVAC system was not operating. In conclusion, the microclimate conditions in the UI Library's manuscript collection room are not ideal for long-term collection preservation, with high temperatures and humidity as well as fluctuations that accelerate degradation. This study recommends optimizing the HVAC system, continuous environmental monitoring, and further research to develop effective mitigation strategies.